Midgut development in rat embryos using microcomputed tomography - Marco Ginzel (Communications Biology, 2021)
Using microcomputed tomography, Ginzel, Martynov et al. provide a modernized exploration of the developing midgut in rat embryos. This study enables three-dimensional, spatial interpretations of key structures throughout development, including the umbilicus and umbilical coelom.